Dinamika Musik Melayu Modern di Kota Medan: Kajian Historis, 1980-2000 - Aulia, Atikah; Ali, M. Nasihudin (Medan Resource Center, 2024)
This research aims to explain the Development of Malay Music in Medan City from 1980-2000. The lack of public knowledge about traditional Malay Deli music which is rarely heard and performed in the community in Medan city is the background of this research. The research used a qualitative method with the theory of historical method. Data collection was done through two stages, namely interviews and documentation. The results showed that Malay music is a folk music that is passed down from generation to generation. Malay music functions as a means to convey moral messages and advice that can provide new ideas, is universal so that the message it conveys can be accepted by everyone. In its development, Malay music has been collaborated with many instruments, elements and other musical genres, which are then packaged in an attractive package to be heard. This research also found that the original Malay musical instruments are actually the pak pung drum, accordion and violin.